The bell bandit - Davies, Jacqueline, 1962- (Davies, Jacqueline, 1962- Lemonade war series, 2012)
Siblings Evan and Jessie must solve the mystery of a missing cherished family treasure while coming to terms with their beloved grandmother's unsettling behavior.